Kaidah Nāsikh dan Mansūkh pada Ayat Kebolehan Menikahi Ahl Al-Kitâb : Studi Komparatif dalam Tafsir Fii Zhilâl Al-Qur’ân dan Al-Azhar - Abdul Muiz; Agung Saputra (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
Allah Swt conveyed the Shari’ah through the Prophet Muhammad Saw with messages explicitly stated in the holy book, the Qur’ān. However, some of the Shari’ah rulings revealed by Allah Swt may appear to be textually contradictory, leading to legal issues in their implementation. One such case is the apparent contradiction between Surah Al-Baqarah (2:221) and Surah Al-Ma'idah (5:5). In this context, the author raises two main research focuses: how Sayyid Quthb and Hamka view the theory of Nāsikh and Mansūkh (abrogation in the Qur’ān), and how they interpret the permissibility of marrying women from Ahl Al-Kitâb (People of the Book). To answer these research questions, the researcher employs descriptive and interpretative methods. The first step is to describe Sayyid Quthb and Hamka’s interpretations of the two mentioned verses. The second step is to compare their interpretations regarding Nāsikh Mansūkh and the ruling on marrying women from Ahl Al-Kitâb. The study finds three key differences and similarities between the two scholars. Both Sayyid Quthb and Hamka affirm the concept of Nāsikh in the Qur’ān, but they differ in how they define the term Nāsikh itself. Both scholars prohibit marriage with polytheistic (Mushrik) women, but they differ in their views on marrying women from Ahl Al-Kitâb. Sayyid Quthb strictly prohibits marrying Ahl Al-Kitâb women, whereas Hamka allows it. Sayyid Quthb argues that Ahl Al-Kitâb no longer exist due to theological deviations among Christians and Jews. In contrast, Hamka maintains that Ahl Al-Kitâb still refers to Jews and Christians, without any time limitation.